The Influence of Motivation, Compensation and Work Discipline toward Employee Performance at PT. Mewah Indah Jaya - Aryani; Daud Arifin; Henry Aspan (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
This research was conducted to explain the partial or simultaneous influence of the variables of motivation, compensation, and work discipline on the performance of employees at PT. Mewah Indah Jaya. The total population used is 70 respondents, employees who work at PT. Mewah Indah Jaya which was taken using a questionnaire as a data collection method in this study. This study uses multiple linear regression analysis. The results of the analysis show that there is a simultaneous significant effect between the three variables, and a partially significant influence between the motivation, compensation and work discipline variables on the performance of employees at PT. Mewah Indah Jaya.